Practical electromagnetics from biomedical sciences to wireless communication - Misra, Devendra 1949- (Wiley-Interscience, 2007)
Practical Electromagnetics discuss electromagnetism, a phenomena involving magnets and electric currents through conductors, thus producing electric and magnetic fields, while integrating engineering applications and fully solved examples.